Pelaksanaan Sistem Manajemen Kesehatan dan Keselamatan Kerja (SMK3) di RS An-Nissa Rejang Lebong Tahun 2024 - Anggrainy Intan Kusuma Putri; Wani Devita Gunardi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The Occupational Health and Safety Management System (SMK3) plays a vital role in ensuring the safety of both healthcare workers and patients within the high-risk environment of hospitals. This study aims to evaluate the implementation of SMK3 at An-Nissa Hospital in Rejang Lebong, covering key aspects such as policy, planning, organization, implementation, evaluation, and continuous improvement. A qualitative research approach with a phenomenological design was used to explore in depth the motivations, attitudes, perceptions, and values influencing SMK3 practices. Data were collected through triangulation techniques, including direct observation, in-depth interviews with key informants, and document analysis consisting of decrees, regulations, and photo evidence related to occupational health and safety activities. The findings indicate that while SMK3 implementation at An-Nissa Hospital is underway, it has not yet fully met the standards outlined in the Hospital Occupational Health and Safety Management Guidelines. Strengthened management commitment and regular evaluations are needed to improve system effectiveness. An optimal SMK3 implementation is expected to create a safe, healthy, and productive work environment for all hospital personnel.